Intrinsic motivation for breast cancer screening among women: a cross- sectional study - Dang, Thi Chau; Nguyen, Thi Ngoc Tu; Ho, Thi Thuy Trang (Tạp chí Y Dược Huế, 2025)
Background: Early detection and timely treatment significantly enhance the odds of beating breast cancer, which is the most prevalent form of cancer among women globally. An individual’s intrinsic motivation plays a pivotal role in determining their willingness to undergo regular cancer screenings. Objective: The purpose of study is to identify factors of intrinsic motivation that affect breast cancer screening. Subjects and Methods: A cross-sectional study was conducted among 649 women living in Da Nang city. The data collection tools included a questionnaire form on participants’ characteristics and the Intrinsic Motivation Inventory tool. In data analysis, descriptive statistics and regression were used. Results: The mean score for intrinsic motivation was calculated as 69.18 ± 8.23. The subscale scores for the intrinsic motivation for breast cancer screening were as follows: perceived usefulness and importance (18.86 ± 2.87), perceived choice and effort (19.80 ± 2.63), perceived interest and relatedness (12.94 ± 1.70), perceived competence (9.41 ± 2.13), pressure and tension (8.18 ±1.33). The most frequent reasons for intrinsic motivation of screening were higher scores for religion (β = 0.12), regular health check-up (β = 0.14), having family history of breast cancer (β = 0.18), regularly receiving breast cancer information (β = 0.10), and having women’s health issues (β =0.14). Conclusions: This study elucidates the factors that influence women’s decisions to engage in opportunistic breast cancer screening. Gaining a comprehensive understanding of these determinants is crucial for developing targeted and effective interventions to enhance screening participation, whether through organized initiatives or opportunistic methods.